The Impact of Project Logbook Usage on Academic Self-Regulation Among Biology Education Students at Universitas Jambi - Sembiring, Dian Arisandy Eka Putra; Yusuf, Muhammad; Mursyd, Danial (Asian Journal of Science Education, 2025)
Higher education institutions in Indonesia are adapting to global challenges, one of which is the implementation of Outcome-Based Education (OBE), which demands innovative teaching approaches like Project-Based Learning (PjBL). This study aimed to evaluate the impact of project logbook usage on academic self-regulation among students in the Biology Education Program at Universitas Jambi. A quantitative, quasi-experimental approach was employed with a two-group posttest-only design. The participants consisted of 170 students, 78 from the third semester and 92 from the fifth semester. Data were collected using the Academic Self-Regulated Learning (A-SRL) questionnaire and analyzed using the Mann-Whitney U test and Spearmans correlation. The results showed no statistically significant difference in self-regulation between students who used project logbooks and those who did not. Additionally, a weak and non-significant correlation was found between logbook usage and self-regulation. These findings suggest that logbooks alone may not substantially enhance self-regulation. Future research should explore combining logbooks with self-regulation training to improve outcomes.